Odpowiedź :
Odpowiedź:
i) 1- (3/4)²= 1- 9/16= 16/16- 9/16= 7/16
j) ( 3/4 - 1/5) :1/2= ( 15/20 - 4/20):1/2= 11/20 *2( skracamy 20 i 2 przez 2)=
= 11/10= 1 i 1/10
k) 1 i 1/7 + 1 i 1/15: 2 i 2/3= 1 i 1/7 + 16/15: 8/3= 1 i 1/7 + 16/15 *3/8( skracamy 16 i
8 przez 8, oraz 15 i 3 przez 3)= 1 i 1/7 + 2/5= 1 i 5/35 + 14/35= 1 i 19/35
l) ( 1 i 3/5 +2,2 ) :6 i 1/3= ( 1 i 3/5 + 2 i 2/10) : 6 i 1/3= ( 1 i 3/5 + 2 i 1/5) : 6 i 1/3=
= 3 i 4/5 : 6 i 1/3= 19/5 : 19/3= 19/5 *3/19( skracamy 19 i 19 przez 19)=
=1/5 *3 = 3/5
m) ( 3 i 4/7 + 11/14) *3,5= ( 3 i 8/14 + 11/14): 3 i 5/10= 3 i 19/14 : 3 i 1/2=
= 61/14 : 7/2= 61/14 * 2/7( skracamy 14 i 2 przez 2= 61/7*1/7= 61/49=
= 1 i 12/49
n) ( 6,25 - 2 i 1/2 ) : 2 i 1/7 -1= ( 6 i 1/4 -2 i 1/2) : 2 i 1/7-1=
= ( 6 i 1/4- 2 i 2/4) : 2 i 1/7-1= ( 5 i 5/4-2 i 2/4): 2 i 1/7-1= 3 i 3/4 : 2 i 1/7-1=
= 15/4 : 15/7-1= 15/4 * 7/15 -1 ( skracamy 15 i 15 )= 1/4*7-1= 7/4-1=
= 1 i 3/4-1= 3/4
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]i)\ \ 1-(\frac{3}{4})^2=1-\frac{9}{16}=\frac{16}{16}-\frac{9}{16}=\frac{7}{16}\\\\\\j)\ \ (\frac{3}{4}-\frac{1}{5}):\frac{1}{2}=(\frac{15}{20}-\frac{4}{20})\cdot2=\frac{11}{\not20_{10} }\cdot\not2^1=\frac{11}{10}=1\frac{1}{10}\\\\\\k)\ \ 1\frac{1}{7}+1\frac{1}{15}:2\frac{2}{3}=1\frac{1}{7}+\frac{16}{15}:\frac{8}{3}=1\frac{1}{7}+\frac{\not16^2}{\not15_{5}}\cdot\frac{\not3^1}{\not8_{1}}=1\frac{1}{7}+\frac{2}{5}=1\frac{5}{35}+\frac{14}{35}=1\frac{19}{35}[/tex]
[tex]l)\ \ (1\frac{3}{5}+2,2):6\frac{1}{3}=(1\frac{3}{5}+2\frac{1}{5}):6\frac{1}{3}=3\frac{4}{5}:6\frac{1}{3}=\frac{19}{5}:\frac{19}{3}=\frac{\not19}{5}\cdot\frac{3}{\not19}=\frac{3}{5}\\\\\\m)\ \ (3\frac{4}{7}+\frac{11}{14})\cdot3,5=(3\frac{8}{14}+\frac{11}{14})\cdot\frac{35}{10}=3\frac{19}{14}\cdot\frac{7}{2}=\frac{61}{\not14_{2}}\cdot\frac{\not7^1}{2}=\frac{61}{4}=15\frac{1}{4}[/tex]
[tex]n)\ \ (6,25-2\frac{1}{2}):2\frac{1}{7}-1=(6,25-2,5):\frac{15}{7}-1=3,75:\frac{15}{7}-1=\frac{375}{100}:\frac{15}{7}-1=\\\\=\frac{\not15}{4}\cdot\frac{7}{\not15}-1=\frac{7}{4}-1=1\frac{3}{4}-1=\frac{3}{4}[/tex]